2022
DOI: 10.3389/fnut.2022.973332
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of global research on vitamin D and reproductive health between 2012 and 2021: Learning from the past, planning for the future

Abstract: BackgroundVitamin D plays an invaluable role in reproductive health, but vitamin D insufficiency and deficiency are generally common among couples of childbearing age and pregnant women. This study aimed to evaluate the evolution, development trend, and research hotspot of publications on vitamin D and reproductive health.MethodsThe literature on vitamin D and reproductive health between 2012 and 2021 was retrieved from the Web of Science Core Collection (WoSCC). We used VOSviewer and CiteSpace to analyze publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…What’s more, the scientific contribution of a researcher can be assessed using the H index. It denotes that a researcher has produced H articles, and each of those papers has received at least H citations from other publications ( 14 ). Additionally, it can also define the publication output of a country/region, institution or journal ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…What’s more, the scientific contribution of a researcher can be assessed using the H index. It denotes that a researcher has produced H articles, and each of those papers has received at least H citations from other publications ( 14 ). Additionally, it can also define the publication output of a country/region, institution or journal ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sum of times cited and average citations per item reflects the level of attention ( Taubes, 1993 ). The H-index reflects the number and quality of an author’s publications, which means that a scholar has published H papers, each of which has been cited at least H times by other publications ( Roldan-Valadez et al, 2019 ; Lu et al, 2022 ). In addition, it can now also define the publication quality of a country/region, institution or journal ( Noruzi et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The search terms were TS = ("distraction osteogenesis" OR "bone lengthening") and document types: (Article OR Review). We selected publications with publication dates ranging from 1 January 1980 to 31 December 2021. cited at least H times by other publications (Roldan-Valadez et al, 2019;Lu et al, 2022). In addition, it can now also define the publication quality of a country/region, institution or journal (Noruzi et al, 2022).…”
Section: Search Strategymentioning
confidence: 99%
“…A bibliometric analysis by evaluated the evolution, development trend, and research hotspot of publications on vitamin D and reproductive health (Lu et al, 2022). The study showed steady growth in annual publication outputs on vitamin D and reproductive health, with multidisciplinary intersection contributing to in-depth exploration in this field.…”
Section: Research and Development In Reproductive Healthmentioning
confidence: 99%
“…The study showed steady growth in annual publication outputs on vitamin D and reproductive health, with multidisciplinary intersection contributing to in-depth exploration in this field. The analysis revealed that low birth weight, adipose tissue, marker, and embryo had a citation burst lasting until 2021, indicating these are the current hotspots in the research on vitamin D and reproductive health (Lu et al, 2022).…”
Section: Research and Development In Reproductive Healthmentioning
confidence: 99%